Quantum uncertainty in the beam width for optical spatial modes - Chille, Vanessa; Aiello, Andrea; Banzer, Peter; Leuchs, Gerd; Marquardt, Christoph; Treps, Nicolas; Fabre, Claude (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We theoretically investigate the quantum uncertainty in the width of optical beams. Many optical applications such as imaging and beam focusing are limited by the quantum noise in spatial characteristics of light beams.
CRIS-Team Scopus Importer:2022-06-05